Interferon Signaling Is Frequently Downregulated in Melanoma - Alavi, Sara; Stewart, Ashleigh Jacqueline; Kefford, Richard F.; Lim, Su Yin; Shklovskaya, Elena; Rizos, Helen (Frontiers in Immunology, 2018)
Immune checkpoint inhibitors that block the PD-1/PD-L1 pathway have significantly improved the survival of patients with advanced melanoma. Immunotherapies are only effective in 15-40% of melanoma patients and resistance is associated with defects in antigen presentation and interferon signaling pathways. In this study, we examined interferon-γ (IFNγ) responses in a large panel of immune checkpoint inhibitor-naïve melanoma cells with defined genetic drivers; BRAF-mutant (n=11), NRAS-mutant (n=10), BRAF/NRAS wildtype (n=10), and GNAQ/GNA11-mutant uveal melanomas (n=8). Cell surface expression of established IFN downstream targets PD-L1, PD-L2, HLA-A, -B and -C, HLA-DR and NGFR were analyzed by flow cytometry. Basal cellular expression levels of HLA-A, -B, -C, HLA-DR, NGFR and PD-L2 predicted the levels of IFN-stimulation, whereas PD-L1 induction was independent of basal expression levels. Only 13/39 (33%) of the melanoma cell tested responded to IFNγ with potent induction of all targets, indicating that downregulation of IFN signaling is common in melanoma. Additionally, we identified two well-recognized mechanisms of immunotherapy resistance, the loss of B2M and IFNGR1 expression. We also examined the influence of melanoma driver oncogenes on IFN signaling and our data suggests that uveal melanoma have diminished capacity to respond to IFN, with lower induced expression of several targets, consistent with the disappointing response of uveal melanoma to immunotherapies. Our results demonstrate that melanoma responses to IFNγ are heterogeneous, frequently downregulated in immune checkpoint inhibitor-naïve melanoma and potentially predictive of response to immunotherapy.